Influence of Differentiation Strategy on Financial Performance of Deposit-Taking Saccos in Kenya - Mutuku, Kioko; Oloko, Margaret; Muturi, Willy (European Journal of Business and Strategic Management, 2024)
Purpose: The purpose of the study was to assess the influence of differentiation strategy on the financial performance of deposit-taking SACCOs in Kenya. Methodology: A descriptive research cross-sectional approach was applied. The target population of this study was 174 DT-SACCOs in Kenya. The sample size was 227 respondents. Structured questionnaires were used to collect primary data from the selected respondents. Data collection method was by use of questionnaires. Quantitative data was analyzed descriptively and inferentially. Descriptive data was analyzed through measures of central tendency including means, standard deviations, frequencies and percentages. Data was coded and analyzed using the Statistical Package for Social Sciences (SPSS v23.0). Results were then presented in tables, diagrams and charts. Findings: The results showed that differentiation strategy had a positive and significant relationship to financial performance (r=0.590, p=0.000; R2=0.348, Î²=1.039). The findings emphasize the importance of implementing effective differentiation strategies to achieve better financial performance. Unique Contribution to Theory, Practice and Policy: The study recommended that deposit-taking SACCOs in Kenya prioritize the implementation of differentiation strategies to enhance their financial performance. By adopting these strategies, SACCOs can position themselves for improved financial success and sustained growth in the highly competitive financial services sector. The study's findings contribute to academic theory by offering significant insights and presents practitioners in strategic management, policy makers, and the leadership in SACCOs with valuable recommendations. They are able to utilize the findings from the current study based on how to model dynamic capabilities that will ensure their knowledge and practicality of competitiveness is beefed up.